The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages much as the ill-health, waste of capacity, and human misery that results from the absence of such services. But the cost of social services falls heavily upon the rich tax-payer and employer, while the cost of the waste, ill-health and misery falls on the rest of us, so naturally they consider the latter more economical. In the demand for the implementation of this programme is implied the demand for a government which sees as its first responsibility the welfare of the people, and is not afraid to provide for this at the expense of the small class who live on large profits. Such a government would not be afraid to acquire the land needed for housing schemes at a price unfavourable to the landowners, or to increase wages and improve conditions for railway workers at the expense of the shareholders. Printed by Wadsworth & Co., Keighley [T.U. all Depts.] and published by Today and Tomorrow Publications, Ltd., 176, Kew Road, Richmond, Surrey. 15X/2/464/1